Psychiatric Assessment and Management of Clients Undergoing Cosmetic Surgery: Overview and Need for an Integrated Approach - Bascarane, Sharmi; Kuppili, Pooja P.; Menon, Vikas (Indian Journal of Plastic Surgery, 2021)
Background Psychiatric disorders are more common among people undergoing cosmetic procedures than the general population and evaluating mental health can be cumbersome for plastic surgeons. We aim to summarize the available literature in this regard and propose an integrated approach to psychiatric assessment and management of mental health issues among this group.Methods Electronic search of MEDLINE, Google Scholar, and PsycINFO databases was done to identify relevant peer-reviewed English language articles from inception till April 2020. Generated abstracts were screened for their eligibility. Included articles were grouped according to their thematic focus under the following headings; prevalence of psychiatric morbidity among clients posted for cosmetic surgery, assessment tools, and management of psychiatric morbidity in relation to undergoing cosmetic surgery.Results A total of 120 articles were reviewed. The prevalence of psychiatric disorder in patients undergoing cosmetic surgery was 4 to 57% for body dysmorphic disorder (BDD); the corresponding figures for depression, anxiety, and personality disorder were 4.8 to 25.8, 10.8 to 22, and 0 to 53%, respectively. A range of tools have been used to assess these disorders and specific measures are also available to assess clinical outcomes following surgery. Screening for these disorders is essential to prevent unnecessary surgical procedures, as well as to ensure timely management of the psychiatric comorbidity.Conclusion Psychiatric morbidity is a common concomitant in cosmetic surgery. A structured and integrated approach to evaluation and management of psychiatric morbidity will help to optimize postsurgical outcomes.
Keywords: psychiatry; cosmetic surgery; depression; India; plastic surgery